IMPROVING TEACHER PERFORMANCE IN LEARNING MANAGEMENT THROUGH TEACHING SUPERVISION AT SD NEGERI 1 NGASINAN, PONOROGO DISTRICT - Supriyadi Supriyadi (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The behavior of academic supervision is directly related to and influences teacher behavior. This means that through academic supervision, supervisors influence teacher teaching behavior so that their behavior is getting better in managing teaching and learning. Furthermore, good teacher teaching behavior will influence student learning behavior. Thus that the implementation of the principal's academic supervision can improve the management of learning if this is done in accordance with the applicable supervision principles. Therefore, the principal as a supervisor is required to be competent as a person who provides guidance to teachers in improving learning management. Procedures for implementing academic supervision consist of: (1) Preparation Stage, including; (a) preparing instruments and (b) preparing a joint schedule, (2) Implementation Phase, namely the implementation of school principal supervision observations, (3) Reporting Stage, including; (a) identify the results of observations during class observations, (b) analyze the results of supervision, (c) evaluate jointly between the principal and teacher, and (d) make notes on the results of supervision which are documented as reports, (4) Follow-up Stage, includes; (a) discussing and making solutions together, (b) notifying the results of class visits, and (c) communicating to the teacher. The results of this study indicate that the implementation of academic supervision in cycle 2 in the learning category is very good with a value of 4.2. With the results mentioned above, the implementation of academic supervision is considered successful because the results are good and are in accordance with the success indicators that have been determined in increasing teacher professionalism.